8D.02: PERIPHERAL PLASMA 18-OXOCORTISOL CAN DISCRIMINATE UNILATERAL ADENOMA FROM BILATERAL DISEASES IN PRIMARY ALDOSTERONISM PATIENTS. (June 2015) - Satoh, F.; Morimoto, R.; Ono, Y.; Iwakura, Y.; Omata, K.; Kudo, M.; Tkase, K.; Seiji, K.; Gomez-Sanchez, C.; Rainey, W.; Nakamura, Y.; Sasano, H.; et al.
Abstract : Objective: Definitive diagnosis of primary aldosteronism requires a long process, including adrenal venous sampling, which currently represents the only reliable method to distinguish unilateral from bilateral diseases. In this study, we attempted to determine whether peripheral plasma levels of 18-oxocortisol and 18-hydroxycortisol could contribute to the clinical differentiation between aldosteronoma and bilateral hyperaldosteronism. Design and method: This study included 234 primary aldosteronism patients including CT-detectable aldosteronoma (APA) (n = 113) and bilateral hyperaldosteronism (BHA) (n = 121), all of whom underwent adrenal venous sampling. All aldosteronomas were surgically resected and their diagnosis was both clinically and histopathologically confirmed. Both 18-oxocortisol and 18-hydroxycortisol were measured using liquid chromatography tandem mass spectrometry. Results: ROC analysis of 18-oxocortisol discrimination of adenoma from hyperplasia demonstrated sensitivity/specificity of 0.83/0.99 at a cutoff value of 4.7 (ng/dL), compared to that based upon 18-hydroxycortisol (sensitivity/specificity: 0.62/0.96). 18-oxocortisol levels above 6.1 ng/dL and/or of aldosterone above 32.7 ng/dL were found in 95 of 113 aldosteronoma patients (84%) but in none of 121 bilateral hyperaldosteronism, 30 of whom harbored CT-detectable unilateral nonfunctioning nodules in their adrenals. In addition, 18-oxocortisol levels below 1.2 ng/dL, the lowest in aldosteronoma, were found 52 out of the 121 (43%) patients with bilateral hyperaldosteronism. Further analysis of 27 patients with CT-undetectable micro aldosteronomas revealed that eight of these 27 patients had CT-detectable contralateral adrenal nodules, the highest values of peripheral 18-oxocortisol and aldosterone were 4.8 and 24.5 ng/dL, respectively, both below their cutoff levels indicated above. Conclusions: The peripheral plasma 18-oxocortisol concentrations served not only to differentiate aldosteronoma, but also could serve to avoid unnecessary surgery for nonfunctioning adrenocortical nodules concurrent with hyperplasia or microadenoma. Figure. No caption available. Receiver operating characteristic (ROC) analysis of patients with APA compared to those with BHA as control and distribution plot analysis. A, B, C and D depict ROC curves to analyze the diagnostic value of respectively peripheral 18-oxocortisol (18oxoF), 18-hydroxycortisol (18OHF), aldosterone and aldosterone-renin activity ratio (ARR), to discriminate APA from BHA. E, F, G and H show respectively the distribution of peripheral 18-oxo-cortisol, 18-hydroxycortisol, aldosterone and aldosterone-renin activity ratio in APA and BHA.